Prevalence and Characterization of Salmonella Species on U.S. Swine Sites as Part of the NAHMS 2021 Swine Enteric Study - Stephanie C. Hempstead; Catherine A. Gensler; Charles A. Haley; Alyson M. Wiedenheft; James B. Robertson; Paula J. Fedorka-Cray; Megan E. Jacob (Journal of Food Protection)
Salmonella species are an important cause of systemic and gastrointestinal disease in animals and humans worldwide; they are also increasingly resistant to multiple classes of antimicrobials which may aid in their treatment and control. Salmonella can also be shed asymptomatically. The aim of this study was to survey the U.S. swine industry to determine and update estimates of Salmonella prevalence, antimicrobial resistance (AMR), replicon distribution, and biofilm potential as part of the United States Department of Agriculture (USDA) National Animal Health Monitoring System (NAHMS) 2021 Swine Study. A total of 1,043 fecal samples were collected from finishing swine 20 weeks and older on 39 sites, from November 2021 through April 2022. Salmonella detection was culture-based and antimicrobial susceptibility was determined by broth microdilution; replicon typing was completed by PCR. Biofilm potential was assessed using a crystal violet assay and normalized to a positive control strain. Overall, the prevalence of Salmonella in swine feces was low (3.9%; 41 of 1,043) and comprised of a broad range of serotypes including S. Derby (34.1%) and S. I 4,[5],12:i:- (22.0%), also found previously. Resistance to at least one antimicrobial agent was detected in 61.0% of isolates with the most prevalent resistance to tetracycline (53.7%). Multidrug resistance (≥3 antimicrobial classes) was found in 26.8% of isolates. The most prevalent replicon types detected were IncHI2 (24.4%) and IncA/C (24.4%), both of which have previously been associated with Salmonella isolated from swine. The majority (85.4%) of isolates formed some biofilm in vitro, characterized as weak (36.6%), moderate (39.0%), or strong (9.8%), with no major associations among common serotype or AMR pattern. Surveillance programs updating the prevalence and characteristics of Salmonella in the U.S. swine population will inform ongoing farm-level and public health efforts to mitigate animal and human health risks.